The Wire - The Complete Fourth Season Episode 1-13 - Chappelle, Joe; Moore, Christine; Mann, Seith; Fine, Russell Lee; West, Dominic; Doman, John; Faison, Frankie (HBO Video, 2007)
With the fall of the Barksdale empire, and the ascent of a new young drug king in Baltimore, McNolty, Bunk and the rest of the detail continue to "follow the money" up the political ladder amidst a hotly contested mayoral campaign. Prez witnesses first-hand the role of inner-city education in the formation of youth as four students, Michael, Namond, Randy and Dukie, face dangerous decisions and adolescent angst in a city rife with the temptations of crime and easy money. The explosive fourth season of The Wire continues to blur the lines between good and evil, and incite the fires of urban unrest. [Cover]
Keywords: DVD-Video